2003
DOI: 10.1046/j.1365-2044.2003.02999.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intra‐operative magnesium sulphate on pain relief and patient comfort after major lumbar orthopaedic surgery

Abstract: SummaryThe effects of intra-operative magnesium sulphate on pain relief after major lumbar surgery were investigated in 24 patients. Patients were randomly allocated to receive either an infusion of 50 mg.kg )1 magnesium sulphate or an equivalent volume of saline at induction of anaesthesia. Anaesthesia was induced with propofol and remifentanil. Tracheal intubation was facilitated using rocuronium. Maintenance was achieved with remifentanil and sevoflurane in nitrous oxide ⁄ oxygen. Intra-operative monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 14 publications
6
95
0
5
Order By: Relevance
“…The results showed that in the group receiving magnesium, postoperative pain scores, and consumption of analgesics during surgery were lower than those of the patients in the control group were. In addition, recovery of neuromuscular block was longer than magnesium sulfate group (17). The mechanism of analgesic effect of magnesium is not entirely clear; however, it seems interfering with calcium channels and NMDA receptors play an important role in this regard.…”
Section: Discussionmentioning
confidence: 87%
“…The results showed that in the group receiving magnesium, postoperative pain scores, and consumption of analgesics during surgery were lower than those of the patients in the control group were. In addition, recovery of neuromuscular block was longer than magnesium sulfate group (17). The mechanism of analgesic effect of magnesium is not entirely clear; however, it seems interfering with calcium channels and NMDA receptors play an important role in this regard.…”
Section: Discussionmentioning
confidence: 87%
“…Many studies evaluating. 5 the effect of magnesium sulphate in postoperative analgesia have not measured the postoperative sedation scores. These results are different from the studies where patients receiving magnesium sulphate were not observed to be sedated in spite of using magnesium sulphate as bolus and/or infusion.…”
Section: Discussionmentioning
confidence: 99%
“…(13) 4 'ın postoperatif morfin tüketimi üzerine etkilerini karşılaştırdıkları çalışmalarında, çalışma ajanları ile morfin tüketiminde bir azalma elde edemediklerini bildirilmişlerdir. Buna karşın magnezyum uygulamasının intraoperatif anestetik ve analjezik ihtiyacını, postoperatif ağrıyı ve analjezi tüketimini azalttığını bildiren çok sayıda çalışma da mevcuttur (14,15). Apan ve ark.…”
Section: Discussionunclassified